The Privacy Of The Legal Nature Of Electronic And Digital Currency - صالح , فواز; الجامع, دينا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Modern technologies have entered all areas of human life. Technological progress and the resulting innovations have led to a radical change in the means of concluding actions and transactions and created new methods and different tools in an era called the era of technology. With the spread of the use of the Internet as one of the most important means of this era, we have a new space that has been termed the cyberspace, which is formed in the sense that we want to use it from a set of digital data, which is the container of information and the mediator that forms communications, which is called the network. Through the communication protocol and the link between the components of the first and second levels, the cyberspace is formed and activated. The economic field is one of the most important areas in which activities related to it have been practiced in this new space, and money plays a very important role in that field by performing its functions represented in the role of financial intermediation in local, regional or international exchanges, and throughout its history it has witnessed great developments in the form and content, and money is still going through stages of development until the present time, especially as technical progress in the field of information and communication technology plays a major role in this field, which led to the emergence of currencies with digital representation, including electronic currency and digital currency.